The Influence of CEO Character on Tax Avoidance In Property And Real Estate Companies Listed on The Indonesia Stock Exchange 2020-2021 - Nanda Resqy Annisa; Hasnawati Hasnawati (Return : Study of Management, Economic and Bussines, 2023)
This study analyzes and obtains empirical evidence on CEO character, including CEO age, CEO tenure, CEO education level, and CEO gender in tax avoidance. This study uses a sample of the property and real estate sectors listed on the Indonesia Stock Exchange (IDX) during the 2020-2021 period. The number of companies that are sampled are 64 companies with observations for two years using the purposive sampling method-the hypothesis testing of this study uses multiple regression models. The results showed that the CEO's education level and CEO's age had a positive effect on tax avoidance. While CEO tenure, gender does not affect tax avoidance.